EVALUATION OF LAND ACQUISITION POLICY FOR THE REVITALIZATION OF DEAD RIVERS IN SAMARINDA CITY - Dyah Rahayuning Perwitasari; Rahman, Ramadhan Aunur (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This research aims to see the extent of the evaluation of land acquisition policies for revitalizing dead rivers in Samarinda City (a case study of JL. D.I Panjaitan – JL. P.M. Noor in Temindung Permai Village in Samarinda City). This type of research is qualitative, and the method used in this research is descriptive. This research will focus on policy evaluation by looking at effectiveness, efficiency, adequacy, leveling, responsiveness, and accuracy, as well as supporting and inhibiting factors in evaluating land acquisition policies for revitalizing the Dead River in Samarinda City. The results of this research illustrate that the evaluation of land acquisition policies for revitalizing the Dead River on Jl. D.I Panjaitan – P.M. Noor Samarinda City has run well based on six indicators from the policy evaluation. The supporting factors in this research are good cooperation between the stakeholders involved and the inhibiting factors in this research. The lack of adequate funding and labor can slow down the progress of river revitalization and conflicts related to land acquisition, causing the dead river revitalization process to be hampered.